Ecuador: Between Developmentalism and Counterinsurgency During the Rodríguez Lara Dictatorship - Moncada, Tamara (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
This essay challenges the myth of the “island of peace” by analyzing the coexistence of progress and repression under Rodríguez Lara. Although associated with the oil boom, the regime implemented a “shock doctrine” that included states of emergency, special courts, and restrictions on strikes. The text highlights state crimes, such as the deaths of Rosita Paredes and Lázaro Condo, demonstrating that nationalist development required coercive tactics to silence social dissent.